Antinomy of Community Participation Rights in the Law on the Environmental Sector - Febriansyah Ramadhan; Ilham Dwi Rafiqi (Jurnal Daulat Hukum, 2021)
Issues of deprivation of rights and discrimination are topics that are always discussed in Indonesia, which is known as a democracy. Community participation is one of the important instruments for indicators of the success of democracy in a country which is carried out in various sectors of life. This research will look at how to regulate community participation rights, especially in the development sector and environmental management. This study uses normative juridical research with a statutory and conceptual approach. The results of the study indicate that conceptually the right of community participation in the environmental sector is an elaboration of the guarantee of good and healthy environmental rights. The right to the environment is a procedural right that cannot be separated from other rights. Regulations regarding community participation rights scattered in various environmental sector laws still contain antinomies that result in inconsistencies in the participation model and guarantee legal uncertainty. From here, efforts need to be made, such as ratifying the Declaration of the Right to Development into law and/or enacting a special law on community participation.